Effect of Colonoscopy Volume on Quality Indicators. (12th May 2016) - Pace, David; Borgaonkar, Mark; Lougheed, Muna; Marcoux, Curtis; Evans, Brad; Hickey, Nikita; O'Leary, Meghan; Boone, Darrell; McGrath, Jerry
Abstract : Background . The purpose of this study is to determine if colonoscopy quality is associated with the annual case volume of endoscopists. Methods . A retrospective cohort study was performed on 3235 patients who underwent colonoscopy in the city of St. John's, NL, between January and June 2012. Data collected included completion of colonoscopy (CCR) and adenoma detection rates (ADR). Endoscopists were divided into quintiles based on annual case volume. To account for potential confounding variables, univariate analyses followed by multivariable logistic regression were used to identify variables independently associated with CCR and ADR. Results . A total of 13 surgeons and 8 gastroenterologists were studied. There was a significant difference in CCR ( p < 0.001) and ADR ( p < 0.001) based on annual volume. Following multivariable regression, predictors of successful colonoscopy completion included annual colonoscopy volume, lower age, male sex, an indication of screening or surveillance, and a low ASA score. Predictors of adenoma detection included older age, male sex, an indication of screening or surveillance, and gastroenterology specialty. Conclusion . Higher annual case volume is associated with better quality of colonoscopy in terms of completion. However, gastroenterology specialty appears to be a better predictor of ADR than annual case volume.